Characterization of NLRP13 in inflammasome activity - Yalçınkaya, Mustafa. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
NOD-like receptors (NLRs) are a family of cytoplasmic proteins with members regulating inflammation and apoptosis. NLRP13 is a novel PYRIN domain containing NLR family member and the roles of NLRP13 in these pathways is still unknown. In current literature, there is no paper about NLRP13. NLRP13 expression is very high in oocytes and NLRP13 expression decreases sharply at blastocyst stage. We have previ-ously shown that NLRP13 is mainly localized in the cytoplasm and partially in mito-chondria (% 35) using confocal microscopy experiments. Also, we have shown that NLRP13 weakly interacts with inflammatory proteins ASC and Caspase-1 and an inflammasome-like structure between ASC-Caspase-1 and NLRP13 formed under over-expression conditions. In this thesis, we further characterized NLRP13 by trying to fig-ure out its roles in inflammasome activity and immune regulation mechanisms. Firstly, we show that NRLP13 is recruited to ASC specks that formed after LPS and ATP treat-ment. Secondly, we show that NLRP13 expression decreases upon LPS priming and that ATP is the most potent second signal of NLRP13 inflammasome. Thirdly, we show that NLRP13 increases levels of inflammatory cytokine secretion. NLRP13 polyclonal and monoclonal antibodies were produced and mass spectrometry analysis was done using these antibodies to find the interaction partners of NLRP13. In addition, it can be said that NLRP13 leads to differentiation of monocytes into more M1 macrophage subgroup. Finally, NLRP13 may have roles in the regulation of inflammation at maternal-fetus in-terface during pregnancy.
Keywords: Inflammation -- Mediators.; Inflammation -- Pathophysiology.